DISCUSSIONS ON FINANCIAL-INDUSTRIAL GROUP: THE ORIGIN AND СONCEPTUALIZATION, AS A GROUP OF PROFITABLE LEGAL ENTITIES - Александр, Кузнецов (SWorldJournal, 2021)
The financial-industrial group is a group of enterprises that has the same decision pole and is created to achieve a relevant division of the economy in order to dynamically analyze it.Having been active for several decades, however, the discussions on